2013
DOI: 10.1007/s00441-013-1753-0
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatin inhibits activation and migration of neutrophils

Abstract: There is a critical need to identify molecules that modulate the biology of neutrophils because activated neutrophils, though necessary for host defense, cause exuberant tissue damage through production of reactive oxygen species and increased lifespan. Angiostatin, an endogenous anti-angiogenic cleavage product of plasminogen, binds to integrin αvβ3, ATP synthase and angiomotin and its expression is increased in inflammatory conditions. We test the hypothesis that angiostatin inhibits neutrophil activation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
0
17
0
1
Order By: Relevance
“…The plasminogen-derived cleavage product angiostatin, which exerts anti-angiogenic properties, was shown to also act as an inhibitor of neutrophil recruitment in vitro and in acute inflammation by interfering with β1- and β2-integrin-dependent adhesion to extracellular matrix proteins and endothelium [66]. More recently, the anti-inflammatory actions of angiostatin were expanded, as it was shown to block neutrophil recruitment by inhibiting MAPK signaling and reactive oxygen species production [67]. Furthermore, in the context of autoimmune arthritis, Blazek et al showed that IFN-λ2/IL-28A can block neutrophil recruitment by acting via its cognate receptor IL-28RA on neutrophils [68].…”
Section: Modulators and Inhibitors Of Neutrophil Recruitmentmentioning
confidence: 99%
“…The plasminogen-derived cleavage product angiostatin, which exerts anti-angiogenic properties, was shown to also act as an inhibitor of neutrophil recruitment in vitro and in acute inflammation by interfering with β1- and β2-integrin-dependent adhesion to extracellular matrix proteins and endothelium [66]. More recently, the anti-inflammatory actions of angiostatin were expanded, as it was shown to block neutrophil recruitment by inhibiting MAPK signaling and reactive oxygen species production [67]. Furthermore, in the context of autoimmune arthritis, Blazek et al showed that IFN-λ2/IL-28A can block neutrophil recruitment by acting via its cognate receptor IL-28RA on neutrophils [68].…”
Section: Modulators and Inhibitors Of Neutrophil Recruitmentmentioning
confidence: 99%
“…It can be explained by the fact that angiostatins exhibit potent antagonizing action toward VEGF, resulting in mitochondrial damage and activating apoptotic signaling pathway in endothelial cells [20]. Moreover, angiostatin proteins have been shown to inhibit neutrophil activation, induce apoptosis and block neutrophil recruitment [21]. Meanwhile, neutrophils are known to be the predominant cell type in the early inflammation phase and play very important role in wound healing by regulating inflammation, debridement of necrotic tissue, phagocytosis of infectious agents and producing various mediators and growth factors [22].…”
Section: Resultsmentioning
confidence: 99%
“…It inhibits recruitment of macrophages ( Distler et al 2002 ; Chavakis et al 2005 ; Dineen et al 2008 ; Lee et al 2009; Chen et al 2011 ; Li et al 2011 ; Lin et al 2011 ), which are normally attracted into the stroma by signaling involving VEGFR-1 and VEGFR-2 ( Li et al 2011 ) and which are involved with completing vascular circuits with VEGFR-3 ( Tammela et al 2011 ). Angiostatin has recently been shown to inhibit migration and activation of neutrophils ( Aulakh et al 2014 ).…”
Section: Anti-angiogenic Agentsmentioning
confidence: 99%